Intense laser field effects on the linear and nonlinear intersubband optical properties of a semi-parabolic quantum well (2011)
ABSTRACT: By using the compact-density matrix approach, the effect of a nonresonant intense laser field on the linear and nonlinear optical absorptions based on intersubband transitions and the refractive index changes in an asymmetric semiconductor quantum well have been presented. Our results show that the peak position of the absorption coefficient is sensitive to intense laser field, the absorption maximum shifts towards lower energies for increasing intense laser field value. Also we observe as the intense laser field strength increases, the total refractive index change has been increased in magnitude and also shifted towards lower energies. The results indicate that linear and nonlinear optical properties of the low dimensional semiconductor heterostructures can be adjusted in a desired energy range by using intense laser field